2013
DOI: 10.5664/jcsm.2978
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Severity of Obstructive Sleep Apnea in Severe Obesity: The Impact of Ethnicity

Abstract: Severely obese South Asians had significantly greater prevalence and severity of OSA than white Europeans. OSA may contribute to increased cardiovascular risk in South Asians compared to white Europeans with severe obesity. Mechanisms mediating the observed associations between these ethnicities require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
35
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 28 publications
5
35
2
5
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Two other studies compared the prevalence of OSA in South Asians and White Europeans in the context of the metabolic syndrome and/or obesity rather than diabetes, and the results were conflicting. 35,36 In one, the prevalence of OSA was 28.3% and there was no difference between South Asians and White Europeans. This study was conducted in a primary care population, however, and utilized the Berlin Sleep questionnaire, 36 whereas our study utilized home-based sleep studies offering more in-depth assessment of OSA.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Two other studies compared the prevalence of OSA in South Asians and White Europeans in the context of the metabolic syndrome and/or obesity rather than diabetes, and the results were conflicting. 35,36 In one, the prevalence of OSA was 28.3% and there was no difference between South Asians and White Europeans. This study was conducted in a primary care population, however, and utilized the Berlin Sleep questionnaire, 36 whereas our study utilized home-based sleep studies offering more in-depth assessment of OSA.…”
Section: Discussionmentioning
confidence: 91%
“…Another study reported a higher prevalence of OSA in South Asians compared to White Europeans (85% versus 66%), despite using the same methodology as ours in diagnosing OSA. 35 There are several factors that may explain this discrepancy. The patients in this study were recruited from a weight management/bariatric clinic rather than a diabetes clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have linked BMI with OSA, although most of the participants in these reports were obese 1,34,35) . It has also been shown that subjects with OSA have a high prevalence of CVD [3][4][5][6] .…”
Section: Discussionmentioning
confidence: 67%
“…Studies point out that Asian subjects who have Obstructive sleep apnea have a greater severity of the condition compared to age and gender controlled groups of whites [17] . Ethnicity and further racial variations of craniofacial anatomical features have been found to determine the rates of occurrence and severity of obstructive sleep apnea between groups.…”
Section: Discussionmentioning
confidence: 99%